THE RELATIONSHIP OF EXCLUSIVE BREASTFEEDING WITH STUNTING INCIDENCES IN THE WORK AREA OF THE TEMPURSARI PONKESDES PUSKESMAS KEDUNGJAJANG LUMAJANG - Ike Yulia Wulandari; Nur Hamim; Iit Ermawati (NHM PRESS, 2023)
Children who are not exclusively breastfed are at higher risk for lack of nutrients needed for growth processes. Growth disorders will cause stunting in children. The purpose of this study was to determine the relationship between exclusive breastfeeding and stunting in Tempursari Ponkesdes, Kedungjajang Health Center, Lumajang Regency. The research design used was causal correlation with a cross sectional design. The sample of this research is mothers who have stunting toddlers aged 6-59 months in June 2022 as many as 34 people using the total sampling technique, the analysis test using the Chi-Square test. The identification of exclusive breastfeeding found that most of the respondents gave non-exclusive breastfeeding (55.9%). In the Tempursari Ponkesdes Working Area, Kedungjajang Health Center, Lumajang Regency, most of the respondent's children experienced stunting in the short category (85.3%). From the Chi-Square test found p>0.05( p = 0.031). It means there is a relationship between exclusive breastfeeding and stunting in the Ponkesdes Tempursari Work Area, Kedungjajang Health Center-Lumajang. It is hoped that health promotion regarding exclusive breastfeeding from birth to the age of 6 months so as to reduce the incidence